Mathematics Learning Model (Based on Multicultural Education) - Masykur, Masykur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research begins with the problem of low mathematics achievement caused by students' neglect of multiculturalism, which can be overcome through mathematics learning based on multicultural education. In line with this, efforts to foster awareness, understanding, tolerance, mutual understanding and national spirit can be developed through multicultural education that is integrated in mathematics learning. Therefore, it is important to develop a mathematics learning model based on multicultural education. Stimulation can be provided through cultural integration in mathematics content as a starting point for students to bring up critical thinking. Methods in this study This research is a study using the method of literature study or literature review. namely a comprehensive overview of the research that has been done on a specific topic to show the reader what is already known about the topic and what is not known, to find rationale for research that has been done or for ideas for further research.From the research it is known that the multicultural education-based mathematics learning model was developed through the integration of content explored from regional cultural wealth, using multicultural contexts in illustrating mathematical concepts or principles. For example, cultural arts artifacts sharpen social sensitivity. Teachers develop socio-cultural norms in the classroom through an acculturation process in order to reduce prejudice and build a conducive school culture so that all students can achieve optimally.